2017
DOI: 10.1016/j.oraloncology.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of high-risk human papillomavirus infection and cancer gene mutations in nonmalignant tonsils

Abstract: The prevalence of high-risk HPV in nonmalignant tonsils is low. High-risk HPV positive tonsils harbored mutations in genes that are commonly altered in HPV-associated head and neck SCC. The role of these mutations in tonsillar carcinogenesis is an interesting target for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
(52 reference statements)
2
15
1
Order By: Relevance
“…The latter finding is consistent with early loss of heterozygosity (LOH) on Chr 11q and 17q in premalignant lesions of the oral cavity (Califano et al 1996). A recent observation that mutations in PIK3CA, EP300, NF1, or RB1 co-occurred with high-risk HPV infections in benign tonsil specimens suggested that they could serve as potential biomarkers for risk of progression (Ilmarinen et al 2017). We anticipate that these data will inform potential secondary prevention strategies for HPV-positive OSCCs among individuals with oral high-risk HPV infections, via genomic profiling of oral rinse or circulating cell-free DNA specimens.…”
Section: Discussionsupporting
confidence: 63%
“…The latter finding is consistent with early loss of heterozygosity (LOH) on Chr 11q and 17q in premalignant lesions of the oral cavity (Califano et al 1996). A recent observation that mutations in PIK3CA, EP300, NF1, or RB1 co-occurred with high-risk HPV infections in benign tonsil specimens suggested that they could serve as potential biomarkers for risk of progression (Ilmarinen et al 2017). We anticipate that these data will inform potential secondary prevention strategies for HPV-positive OSCCs among individuals with oral high-risk HPV infections, via genomic profiling of oral rinse or circulating cell-free DNA specimens.…”
Section: Discussionsupporting
confidence: 63%
“…Regarding the important role of HPV in OPSCC, several studies have investigated the presence of HPV infection in the non-malignant tonsil tissues of cancer-free individuals or in adjacent tumors ( 8 11 ) as well as in the genomic profiles of premalignant lesions prior to oral cancer ( 15 ). Attempts to detect HPV infection in almost 4,000 non-tumor tonsil tissue specimens in the UK did not find evidence of an association with HPV ( 10 ), and two other studies conducted in Finland and in the US found that only 1.0% and 3.1% of patients, respectively, had high-risk HPV infections (in 477 and 5,579 non-malignant tonsil tissues, respectively) ( 9 , 11 ). Nevertheless, in-depth genomic characterization of the normal to premalignant to malignant transition process driven by persistent HPV16 infection in OPSCC has not been performed.…”
Section: Discussionmentioning
confidence: 96%
“…However, intensive efforts to detect active HPV16 in tissues surrounding such tumors have provided scant evidence of this process ( 8 ). In addition, studies examining the prevalence of HPV infection in non-tumor tonsillar specimens have been performed ( 9 11 ) but have failed to find or have found only a low (1%-3.1%) rate of high-risk HPV infection. Thus, HPV-infected non-tumor tissues are rare; and no comparative analyses of HPV-infected non-tumor and corresponding tumor tissues, which might elucidate the precise serial action of HPV, have yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…According to PCR, 2 of the 195 (1.0%) DNA samples isolated from the tonsil tissue were positive for HPV-16 in a German group study [ 30 ]. At the Helsinki University Hospital, 13 of the 206 (6.3%) samples were positive for HPV DNA in a 2001 to 2003 study and 5 of the 477 (1.0%) patients were detected positive for HPV DNA in a 2012 and 2015 study [ 31 , 32 ]. The observation that oral rinse test is less sensitive in the detection of HPV-associated tonsil cancers highlights its limitation as a screening tool.…”
Section: Discussionmentioning
confidence: 99%